1998
DOI: 10.1046/j.1464-410x.1998.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oral selenium supplementation on human sperm motility

Abstract: Objectives  To determine whether the decline in selenium intake and selenium status in men in the West of Scotland might be a contributory factor to male subfertility. Patients and methods  Two semen samples were collected from patients attending a subfertility clinic and those patients with samples showing reduced motility were invited to participate in an ethically approved double‐blind clinically controlled trial with informed consent. Sixty‐nine patients were recruited and received either placebo, selenium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
2
19

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(159 citation statements)
references
References 27 publications
8
130
2
19
Order By: Relevance
“…Fifteen in vivo studies 31,36,41,47,50,51,[62][63][64][65][66][67]69,76,82 included pregnancy rate among the end points measured; in two of these studies, a higher pregnancy rate was achieved, but was not statistically significant. 47,76 In another two studies, the pregnancy rate was lower in the antioxidant-treated group than in the control group, although the comparison was against clomiphene citrate or mesterolone rather than placebo. 50,51 In yet another two studies, no effect was observed on pregnancy rate, and in all of the remaining trials, a statistically significant increase in pregnancy rate was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen in vivo studies 31,36,41,47,50,51,[62][63][64][65][66][67]69,76,82 included pregnancy rate among the end points measured; in two of these studies, a higher pregnancy rate was achieved, but was not statistically significant. 47,76 In another two studies, the pregnancy rate was lower in the antioxidant-treated group than in the control group, although the comparison was against clomiphene citrate or mesterolone rather than placebo. 50,51 In yet another two studies, no effect was observed on pregnancy rate, and in all of the remaining trials, a statistically significant increase in pregnancy rate was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Vezina et al 35 combined selenium and vitamin E, leading to improvements in sperm motility, morphology and viability; however, concentration did not change significantly, as already discussed. In 1998, Scott et al 76 conducted a trial with 64 men (of whom 46 had previously been diagnosed with OAT and 16 were classified as subfertile), administering selenium alone or in combination with vitamins A, C and E at daily doses of 100 mg, 1 mg, 10 mg and 15 mg respectively. No improvement was observed in sperm concentration after 3 months, although motility was increased in treated subjects.…”
Section: Seleniummentioning
confidence: 99%
“…Selenyum ile E vitamini takviyesi yapilan 54 erkek hastada yine ayni sonuç-lar elde edilmiştir. Sperm yoğunluğunda azalma olmamasina rağmen, hareketliliğinde azalma meydana gelmiştir (31,32) .…”
Section: Vi̇tami̇n Ve Mi̇nerallerunclassified
“…The analysis makes possible to directly evaluate the concentrations of the elements of interest in the reproductive cells and seminal fluid, which can determine the semen quality and fertility success. 8,[10][11][12][13][14] The semen analysis is also useful in the evaluation of the exposure to toxic metals in the environment. 1,6 The analysis of trace elements in biological samples is predominantly performed using atomic spectrometry techniques, such as atomic absorption spectrometry (AAS), [15][16][17][18][19][20][21][22][23] inductively coupled plasma emission spectrometry (ICP-OES) 24 and inductively coupled plasma mass spectrometry (ICP-MS).…”
Section: Introductionmentioning
confidence: 99%